Managing integrated interorganizational logistic systems in the digital economy - Gviliya N.A. (Ural State University of Economics, 2019)
The article examines and systematized interorganizational logistic systems defined as organizational-economic forms of establishing and implementing economic relations between micro-logistic systems resistant to changes in the external environment. The methodological basis relies on the provisions of the theory of logistic management including the issues of interfirm and interorganizational interaction that is formed under the influence of the evolutionary factor of logistic integration. The data of the expert survey and analysis of aggregated indicators of logistic intersystem entities functioning in the Russian Federation help to identify the most integrated intersystem logistic entities. The Digital Transformation Index developed by foreign researchers and adjusted to the Russian practice allows us to investigate the depth of logistic integration and the level of digitalization of interorganizational logistic entities. The authors establish that there is an interrelation between the stages of logistic integration evolution and the development of forms of intersystem (interorganizational) logistic entities. The paper proposes a method for evaluating the depth of logistic integration and provides the estimates of this indicator and reference values for the levels of management digitalization for intersystem logistic entities typical of the Russian reality. The research results are of use for business practitioners when choosing management tools for particular forms of interorganizational logistic systems, including the instruments based on digital technology, as well as for scholars studying management in general and logistics and supply chain management, in particular.